Diversity of mosquitoes and their seasonal fluctuation in two wards of Dhaka city - Khan, Humayun Reza; Islam, Md Muzahidul; Akter, Tangin; Karim, Md Rezaul; Farid, Md Sheik (Dhaka University Journal of Biological Sciences, 2014)
The diversity and seasonal fluctuation of mosquitoes were studied in the two Wards (No. 53 and 54) of Dhaka City from March, 2011 to February, 2012. Eleven habitats under six spots, viz. Ramna Park, Hatir Jheel, Siddeshwary field, Moghbazar pond, Wireless lane and Indoor habitats were surveyed. Altogether 13 species of mosquitoes were identified belonging to four genera and these were Culex quinquefasciatus, Cx. gelidus, Cx. vishnui, Cx. fuscocephala, Cx. tritaeniorhynchus, Cx. hutchinsoni, Cx. fatigans, Mansonia annulifera, Mn. uniformis, Mn. indiana, Aedes aegypti, Ae. Albopictus and Armigeres subalbatus. Seven species, e.g. Cx. gelidus, Cx. vishnui, Ae. aegypti, Ae. albopictus, Mn. uniformis, Mn. annulifera and Mn. indiana were dominant in the months from June to October; three species, e.g. Cx. fuscocephala, Cx. quinquefasciatus and Ae. aegypti from November to February; and nine species, e.g. Ae. aegypti, Ae. albopictus, Ar. subalbatus, Cx. fuscocephala, Cx. gelidus, Cx. quinquefasciatus, Cx. tritaeniorhynchus, Cx. vishnui and Mn. annulifera from March to May. Cx. quinquefasciatus was present in all habitats except the fresh water lake. In semi?polluted Jheel, all the mosquito species, except Ae. aegypti, Ae. albopictus and Mn. indiana were observed. In coconut shell, larvae belonging to Cx. quinquefasciatus, Cx. fuscocephala, Ae. aegypti and Ar. subalbatus were observed. In tree holes, Ae. albopictus occupied the highest number. In tubs, Cx. quinquefasciatus, Cx. vishnui, Ae. aegypti and Ae. albopictus were found. In polluted drains, Cx. quinquefasciatus, Cx. vishnui and Cx. gelidus were common, but Cx. quinquefasciatus was the dominant one. In indoor habitat, Cx. quinquefasciatus and Ae. aegypti were more abundant. DOI: http://dx.doi.org/10.3329/dujbs.v23i1.19822 Dhaka Univ. J. Biol. Sci. 23(1): 17-26, 2014